A Patagonian swan (Anatidae: Anserinae) from the Upper Pleistocene of Austral Chaco (Argentina) - Vezzosi, Raúl Ignacio (2022)
A new material of a Quaternary waterfowl is described here. The implications of this finding, in the context of the dispersal of Anatidae in the past, are discussed. The specimen consists in a partial humerus coming from the Upper Pleistocene of austral Chaco from Santiago del Estero Province, Argentina. The specimen here described belongs to the tribe Cygnini, being larger than most members of the clade. The humerus shows different size than with other members of the tribe Cygnini, being larger than the humeri referred to the Andean goose (Oressochen melanopterus), the Sheldgeese of the genus Chloephaga, the Comb Duck (Sarkidiornis sylvicola), and larger than the Ruddy Shelduck (Tadorna ferruginea). However, the humerus have several anatomical characters indicating that it belongs to a basal anserine duck. These combinations of features allow us to assign this fossil to a species of waterfowl: Coscoroba coscoroba. This finding, it context with the history of the South American Cygnini, provides new environmental interpretations associated with wetlands, which will be tested in the austral Chaco and Northern Pampa through future multi-proxy studies.